Genomic structure and insertion sites of Helicobacter pylori prophages from various geographical origins - Vale, Filipa F. (2017)
Helicobacter pylori genetic diversity is known to be influenced by mobile genomic elements. Here we focused on prophages, the least characterized mobile elements of H. pylori. We present the full genomic sequences, insertion sites and phylogenetic analysis of 28 prophages found in H. pylori isolates from patients of distinct disease types, ranging from gastritis to gastric cancer, and geographic origins, covering most continents. The genome sizes of these prophages range from 22.6-33.0 Kbp, consisting of 27-39 open reading frames. A 36.6% GC was found in prophages in contrast to 39% in H. pylori genome. Remarkably a conserved integration site was found in over 50% of the cases. Nearly 40% of the prophages harbored insertion sequences (IS) previously described in H. pylori. Tandem repeats were frequently found in the intergenic region between the prophage at the 3' end and the bacterial gene. Furthermore, prophage genomes present a robust phylogeographic pattern, revealing four distinct clusters: one African, one Asian and two European prophage populations. Evidence of recombination was detected within the genome of some prophages, resulting in genome mosaics composed by different populations, which may yield additional H. pylori phenotypes.